Pemberian Posisi 450 Efektif dalam Meningkatkan Saturasi Oksigen dan Menurunkan Respiration Rate Pasien Congestive Heart Failure (CHF) - Bagus Ananta Tanujiarso (NHM PRESS, 2022)
Indonesia has the highest ranking of deaths from CHF in Asia with 371,000 people. Central Java ranks third in the number of heart failure sufferers in Indonesia. Shortness of breath and impaired oxygenation requirements are important problems in CHF patients. Positioning at 30o, 45o and 60o is expected to have a positive effect on oxygen saturation and respiration rate in CHF patients. This study aims to determine the effect of giving 30o, 45o, and 60o positions on oxygen saturation and respiration rate in CHF patients in the Emergency Room. The research design uses a quasy experiment design method with a times series approach. The sampling technique in this study used purposive sampling, with a total sample of 30 respondents. The data collection tools used in this study were pulse oximetry to measure oxygen saturation, Vital Sign Monitor to measure respiration rate, as well as oxygen saturation observation sheets, respiration rate observation sheets and respondent characteristic questionnaires. In this study, each respondent measured the pre-test of oxygen saturation and respiratory rate before the intervention was carried out, then they were given a position of 30o, 45o, and 60o respectively with the treatment of each position being carried out for 30 minutes, each change in position was measured post-test. The results of this study indicate that the positioning of 30o, 45o and 60o in CHF patients is proven to increase oxygen saturation and reduce respiration rate (shortness of breath) in CHF patients in the ED (P value <0.000). Although all of these position changes affect oxygen saturation and respiratory rate, the 45o position has a better effect in increasing oxygen saturation and reducing the respiratory rate (shortness of breath) in CHF patients compared to 30o and 60o positions.